(untitled) - Jain, Arvind K. (Miami, 1994)
The book presents instruments, practices, and institutions of various segments of international financial markets: international capital markets, risk management in international markets, financial institution markets
Keywords: Capital movements,Financial institutions, international,Foreign exchange administration,International finance,International trade,Thương mại quốc tế,Tài chính quốc tế,Tổ chức tài chính quốc tế